Pengaruh Transparansi dan Akuntabilitas terhadap Tata Kelola Pemerintahan Desa Sirnajaya Kabupaten Bekasi - Tiara Sapitri; Lusian Putri; Joni Mulyadi; Farisha Akeilla Nuralifiyah; Fathihattul Ihsan; Muhammad Hafizh Mahardika; Winona Dea Nur afni (Journal of Economics, Management, and Accounting, 2026)
This study aimed to examine the influence of organizational culture and leadership on employee performance in organizations located in North Cikarang District. A quantitative research approach with a survey method was employed involving 70 respondents selected through purposive sampling. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 3 software. The results revealed that organizational culture had a positive and significant effect on employee performance, with a path coefficient of 0.556, a t-statistic of 6.777, and a p-value of 0.000. Leadership also showed a positive and significant effect on employee performance, with a path coefficient of 0.269, a t-statistic of 2.706, and a p-value of 0.007. The R-square value of 0.425 indicates that organizational culture and leadership jointly explain 42.5% of the variance in employee performance. These findings highlight the importance of strengthening organizational culture supported by effective leadership practices to improve employee performance.